2015
DOI: 10.5539/ibr.v8n9p142
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Healthcare Adoption among Patients in a Developing Country Environment: Exploring the Influence of Age and Gender Differences

Abstract: This research was motivated by two considerations: (1) Mobile-based technologies have the potential to improve the delivery process of healthcare services, and (2) limited research has been implemented worldwide to focus on patients" perceptions towards the adoption of mobile healthcare, particularly in developing country environment. This research proposes an extended TAM model as a research framework to better understand the adoption process of mobile healthcare among patients. To serve the objectives of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 168 publications
(244 reference statements)
2
21
1
Order By: Relevance
“…Technology adoption varies according to age groups whereby older consumers are more anxious (Lee et al, 2010). In the context of health-care systems, age significantly moderates mobile technology usage (Faqih and Jaradat, 2015). In China, age is indicated to significantly affect m-commerce adoption (Chong, 2013).…”
Section: Moderation By Gender Age and Experiencementioning
confidence: 99%
“…Technology adoption varies according to age groups whereby older consumers are more anxious (Lee et al, 2010). In the context of health-care systems, age significantly moderates mobile technology usage (Faqih and Jaradat, 2015). In China, age is indicated to significantly affect m-commerce adoption (Chong, 2013).…”
Section: Moderation By Gender Age and Experiencementioning
confidence: 99%
“…Age strengthens perceived usefulness, perceived cost and perceived system quality and in turn moderates attitude towards intention to adopt mobile banking (Riquelme & Rios, 2010). Faqih and Jaradat (2015) found that demographic variables of age and gender have considerable moderating influence on the adoption of mobile technologies in healthcare systems in Jordan.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is evidenced by several previous research that stated that perceived ease of use (PEU) has a noteworthy impact on one's intention to take and use certain technologies. Research on the implementation of applications for health services in emerging countries has concluded that perceived ease to use has positively affected the acceptance and usage of technology by a person (Faqih & Jaradat, 2015). Chang, Pang, Tarn, Liu, and Yen (2015) have found the same thing in e-hospital acceptance research among people in Taiwan.…”
Section: Mediating Role Of Perceived Usefulness and Perceived Ease Of Usementioning
confidence: 88%